(untitled) (Journal of Environmental Science and Natural Resources, 2021)
Widespread groundwater arsenic contamination in south, south-western and north-eastern regions and high salinity in the south-western coastal region are the two major challenges for drinking water supply in Bangladesh. In this study, we assessed various water supply technologies used for mitigating arsenic and salinity in Laksam of Cumilla and Assasuni of Satkhira district. Water samples were analyzed for Arsenic, Iron, Chloride (indicator for salinity) and FC from different water extraction systems (shallow, deep and Tara tubewells), groundwater arsenic treatment units (SIDKO and READ-F), rainwater harvesting systems (RWH), pond sand filters (PSF), and managed aquifer recharge units. Most shallow tubewells, both in Laksam and Assasuni, have been found to produce arsenic contaminated water. But water from deep and Tara tubewells have been found arsenic-free, though high concentration of iron was observed in the wells in Laksam. Rainwater harvesting systems, PSF and MAR units in Assasuni have been found to provide water free from the common chemical contaminants but suffer from high bacterial contamination. Deep tubewell appear to be the most preferred option where a suitable aquifer is available. The community-scale groundwater treatment systems would require strong operation and maintenance support from the service providers to be successful. Environ. Sci. & Natural Resources, 12(1&2): 215-223, 2019